Faktor-Faktor yang Mempengaruhi Partisipasi Masyarakat Terhadap Pembangunan di Kabupaten Banyumas - Dijan Rahajuni; Endang Sri Gunawati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2009)
The aims of the research are: to find out the condition of the people participation, income distribution, education level, economic growth, and government expenditure, and also to find out and analyze the effects income distribution, education level, economic growth, and government expenditure to the people participation in Banyumas Regency. The data are secondary data that covered: the people participation, income distribution, education level, gross regional domestic product, and government expenditure in Banyumas Regency. The method analysis are tabulation and multiple regression analysis model. The result of 1999–2006 period analysis shows: (1) The everage growth of people participation on 8,29%, economic growth on 3,49%, government expenditure on 20,44%, income distribution on 2,57%, and education level on 4,93% for every year, (2) The effect of the four variables above in people participation have significant effect but in partial only government expenditure variable have significant effect on 5%. Therefore, it is suggested that Banyumas Regency Government should be to attended and give an real example to increase the people participation, economic growth, income distribution, and the level of education with the government expenditure. Keywords: people participation, income distribution, education level, gross regional domestic product, government expenditure